Towards Continuous Delivery for Domain Experts: Using MDE to Integrate Non-Programmers into a Software Delivery Pipeline - Nehls, Holger; Ratiu, Daniel (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
Modern computed tomography (CT) scanners are complex, software-intensive systems whose correct functioning is governed by over 100 parameters which depend on the concrete hardware configurations and on the addressed clinical use-cases. To tame the intrinsic complexity of the parameters configurations, over the last four years, Siemens Healthineers (SHS) have been developing and deploying a set of domain specific languages and tooling based on Jetbrains' Meta-Programming System. In this paper, we report on the challenges and experiences we made while building two delivery pipelines. At meta-level, we built a continuous delivery pipeline such that new versions of our domain specific modeling tool can be deployed continuously based on the feedback of domain experts. At model-level we have integrated the developed domain-specific tool in the continuous delivery pipeline for the computed tomography software and thereby bring the Continuous Delivery mind-set with advantages and challenges to domain experts who are working traditionally "outside" of the software development.